PENINGKATAN MOTIVASI DAN HASIL BELAJAR TENIS LAPANGAN MELALUI PENGGUNAAN MULTIMEDIA DALAM MODEL PENGAJARAN LANGSUNG PADA MAHASISWA S-1 PENJASKESREK JURUSAN PENDIDIKAN OLAHRAGA FIK UNESA - Advendi Kristiyandaru, ; Sapto Wibowo, ; Ayunita Leliana, (Widya Cendika, 2011)
The main problem in learning process of tennis in Physical Education Department, especially S-1 Penjaskesrek, is the students have lack of motivation in participating in tennis classes. In addition, lecturer also still applies old-fashioned teaching methods, i.e. speech, so that less stimulates them to participate actively during class. These conditions led to less student learning outcomes. This can be seen from the results for middle evaluation (middle test), obtained an average value of students were still below the standard that is less than 60, even in a class no one received an A. According to that background, operational problems in this research can be formulated as follows: (a) How does students motivation to learn tennis with the use of multimedia and hand-on teaching model?; (b) How are students learning outcomes in tennis class with the use of multimedia and hand-on teaching model? After did 2 cycles, students motivation to learn tennis has increased (from 122.51 ± 21.049 to 141.49 ± 15.22). Their learning outcomes also increase. As many as 51 students have gotten ≥ 60.